Analisis Kesulitan Belajar Siswa Dalam Pembelajaran Tematik Siswa Kelas III SDN X Kota Batusangkar - Sandela, Putri; Safrizal; Komalasari, Elis (Pendagogia: Jurnal Pendidikan Dasar, 2025)
The research was motivated by the difficulties  experienced by students in thematic learning at SDN X Batusangkar City. This study aims to describe thematic learning difficulties and describe the factors that influence thematic learning difficulties in class III students of SDN X Kota Batusangkar. The method of this research is to use qualitative research methods with the type of research used is a case study. The informants in this study were a class III elementary school teacher and a class III elementary school student, who were selected by purposive sampling technique. The instruments in this study were the researchers themselves and several tools used in conducting the research. Data collection techniques used are interviews, observation, and documentation studies. The data analysis technique uses the Milles and Huberman model with the stages: data collection, data reduction, data display, and drawing conclusions. The validity of the data was tested by triangulation of sources and techniques. The results showed that the difficulties of thematic learning in class III students were 1) students were confused, 2) students who had low thinking power were left behind, 3) student scores were low, 4) students were bored. In conclusion, there are still difficulties experienced by students related to thematic learning. This is caused by many influencing factors.